C-axis Fabric from Physical Properties Samples of the WAIS Divide Ice Core - Alley, Richard; Fitzpatrick, Joan; Voigt, Donald E. (IEDA: US Antarctic Program Data Center, 2015)
This data set contains c-axis fabric measurements and grain area from the physical properties samples taken from the main West Antarctic Ice Sheet (WAIS) Divide ice core, WDC06A , Antarctica.